Dietary supplementation with nano-zinc modulates the expression of the antiviral immune gene IRF3: a novel report - Tah, Amrita; Pal, Aruna; Chatterjee, Paresh Nath; De, Debasis; Mahato, Achinta; Chakraborty, Argha; Debnath, Manti; Roy, Sovan (Frontiers in Immunology, 2025)
In the era of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the application of zinc has increased worldwide. It has the potential to increase the body’s antioxidant status and provide better immune makeup. Currently, zinc is indiscriminately used as a therapeutic agent, and this creates an unwanted antagonism with the other interacting micronutrients that are present in the gut and causes secondary deficiencies of other critical micronutrients, which often leads to various complications. In this study, our aim was to synthesize a nano-sized zinc followed by its dietary fortification. We found that the supplemental nano-zinc has an antiviral effect using milkfish (Chanos chanos) as a model organism. The IRF3 gene was chosen as a molecular marker for antiviral assessment, which has different integral zinc binding sites. For the first time, we have characterized the IRF3 gene in C. chanos and discovered certain important domains as zinc binding sites, as well as other important domains related to antiviral activity, such as the serine protease NS3 activity and the interferon regulatory factor (IRF) tryptophan pentad repeat domain. The expression profile of IRF3 was significantly improved among fish supplemented with dietary nano-zinc, and the best effect was observed in the group provided feed fortified with 40 ppm nano-zinc. The results of this study revealed that nano-zinc can directly be incorporated into IRF3, which increases its bioavailability and improves its antiviral activity through biochemical pathways, as described in the STRING and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses.